2013
DOI: 10.1074/mcp.r112.026005
|View full text |Cite
|
Sign up to set email alerts
|

Glycoproteomic Analysis of Antibodies

Abstract: Antibody glycosylation has been shown to change with various processes. This review presents mass spectrometric approaches for antibody glycosylation analysis at the level of released glycans, glycopeptides, and intact protein. With regard to IgG fragment crystallizable glycosylation, mass spectrometry has shown its potential for subclass-specific, high-throughput analysis. In contrast, because of the vast heterogeneity of peptide moieties, fragment antigen binding glycosylation analysis of polyclonal IgG reli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
149
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(152 citation statements)
references
References 102 publications
3
149
0
Order By: Relevance
“…Although it is well demonstrated that correct assembly of the 21 (or 24, depending on the oligomerization status) polypeptides is a prerequisite for the functionality of IgMs (7), the impact of glycosylation is largely unknown. However, results from clinical studies, particularly on IgGs, indicate that carbohydrates play a structural and functional role for all immunoglobulins (8)(9)(10).…”
mentioning
confidence: 99%
“…Although it is well demonstrated that correct assembly of the 21 (or 24, depending on the oligomerization status) polypeptides is a prerequisite for the functionality of IgMs (7), the impact of glycosylation is largely unknown. However, results from clinical studies, particularly on IgGs, indicate that carbohydrates play a structural and functional role for all immunoglobulins (8)(9)(10).…”
mentioning
confidence: 99%
“…Whereas the glycosylation of IgG, IgE and IgA is well studied, there are no detailed mass spectrometric data available describing the site-specific glycosylation profiles of human serum IgM (6 -9). Human IgG has one conserved Nglycosylation site on each heavy chain CH2 domain at Asn 297, and ϳ15-20% of normal polyclonal IgG bears additional Fab (fragment antigen binding) glycosylation (6,10,11). Other antibody classes such as IgM or IgA show a higher complexity with respect to the number of glycosylation sites and variety of glycoforms (6,9).…”
mentioning
confidence: 99%
“…Human IgG has one conserved Nglycosylation site on each heavy chain CH2 domain at Asn 297, and ϳ15-20% of normal polyclonal IgG bears additional Fab (fragment antigen binding) glycosylation (6,10,11). Other antibody classes such as IgM or IgA show a higher complexity with respect to the number of glycosylation sites and variety of glycoforms (6,9). Only recently, also monoclonal IgM antibodies came into the focus of pharmaceutical industry, because they show great potential for the treatment of diseases (12)(13)(14).…”
mentioning
confidence: 99%
“…ELLA and impedimetric lectin biosensors. Lectins involved in the study were selected to keep in mind an ability to bind to biantennary complex glycan types often present on human IgG (and other proteins) in human sera at relatively high concentrations and known to be aberrantly glycosylated during a progress of specific (mostly autoimmune) diseases [46]. Antibody against BSA was selected as a glycoprotein to perform calibration of lectin microarray technique with eight different lectins.…”
Section: Selection Of Lectinsmentioning
confidence: 99%